Mitigation of backgrounds from cosmogenic 137Xe in xenon gas experiments using 3He neutron capture. (25th May 2020) - Rogers, L; Jones, B J P; Laing, A; Pingulkar, S; Smithers, B; Woodruff, K; Adams, C; Álvarez, V; Arazi, L; Arnquist, I J; Azevedo, C D R; Bailey, K; et al.
Abstract: 136 Xe is used as the target medium for many experiments searching for 0 νββ . Despite underground operation, cosmic muons that reach the laboratory can produce spallation neutrons causing activation of detector materials. A potential background that is difficult to veto using muon tagging comes in the form of 137 Xe created by the capture of neutrons on 136 Xe. This isotope decays via beta decay with a half-life of 3.8 min and a Q β of ∼4.16 MeV. This work proposes and explores the concept of adding a small percentage of 3 He to xenon as a means to capture thermal neutrons and reduce the number of activations in the detector volume. When using this technique we find the contamination from 137 Xe activation can be reduced to negligible levels in tonne and multi-tonne scale high pressure gas xenon neutrinoless double beta decay experiments running at any depth in an underground laboratory.